Notes in Tune: Arts-based Therapy (ABT) at Schizophrenia Awareness Association in Pune, India - Chabukswar, Aanand (International Journal of Psychosocial Rehabilitation, 2016)
The use of the arts as therapy is a paradox in India. Despite a long tradition of healing rituals and practices, there is barely any arts- based model consistent used for contemporary mental health needs and settings. With the aim of introducing and investigating use of ABT (Arts-based Therapy), regular sessions were conducted at Schizophrenia Awareness Association’s day-care centre in Pune, India over a period of eighteen months. The group was heterogeneous, with varied severity of symptoms of schizophrenia. With therapeutic goals of present moment attention and interpersonal engagement, participant responses were recorded through PANSS (Positive and Negative Syndrome Scale), a Rating Scale, a Checklist and qualitative observations. All data sources show definite though variable response to ABT. PANSS scores noted a decline in negative symptoms and general psychopathology, especially the sub-items marked ‘severe’ show a clear trend of reduction. The correlations between PANSS, Rating Scale and Checklist are notable though not statistically significant. The qualitative data uncovers the nuances of the process. Despite a small sample size, the study points in the direction of use of ABT in mental health settings, especially within the Indian context.